Pengaruh Literasi Keuangan Terhadap Pengelolaan Keuangan UMKM Kecamatan Bontonompo Kabupaten Gowa - Asriani N; Nasrullah; Amelia Rezki Septiani Amin (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine how much influence financial literacy has on the financial management of MSMEs in Bontonompo District, Gowa Regency. The population in this study was MSMEs in Bontonompo District, Gowa Regency and used the Slovin formula and a sample of 95 respondents. The type of data used in this study was quantitative, obtained from questionnaires distributed to respondents. Based on the results of the study using statistical calculations through the Social Science (SPSS) version 26 application regarding the influence of financial literacy on the financial management of MSMEs in Bontonompo District, Gowa Regency, it has a positive and significant effect on the financial management of MSMEs in Bontonompo District, Gowa Regency.